Cytotoxic effect of konjac glucomannan on the molecular and dielectric properties of HepG2 and WRL68 liver cell lines / Sakunie Sawai - Sakunie , Sawai (2019)
Hepatocellular carcinoma (HCC) is the most lethal hepatic cancer type in both men and women worldwide due to late diagnosis, inefficient therapeutic outcomes with many side effects as well as disease recurrence. Hence, investigating safer and effective cancer treatment alternative for liver cancer using natural product is the main focus of the present study. Konjac glucomannan (KGM), a water-soluble dietary fibre of Amorphophallus konjac K. Koch has been clinically proven as an effective antioxidant, anti-microbial and laxative agent, intriguingly it is traditionally known for its tumour suppression and prevention properties which remain to be explored. This study thus aimed to determine the potential cytotoxic effect of KGM on hepatic carcinoma cell line, HepG2 and non-malignant hepatic cell line, WRL68 (control) for their viability, proliferation and dielectric properties using molecular and dielectrophoresis biosensor techniques. KGM treatment at the concentration of 3.60 mg/mL resulted in reduced viability of HepG2 cells significantly, in line with the apoptotic-like morphological changes, while WRL68 cell viability remained unaffected. High BAX to BCL2 gene expression ratio suggests that KGM inhibits HepG2 cell viability via activation of Bcl-2/BAX protein pathway. Meanwhile, standard chemo-drug, 5-Fluorouracil (5-FU) remains effectual against HepG2 cells; it does not confer selective inhibition, since the treatment affects the viability of both HepG2 and WRL68 cell lines. In addition, KGM disrupted the dielectric qualities of HepG2 surface membrane which cells undergo apoptosis and experienced p-DEP at crossover frequency (220 kHz). Comparative monosaccharide D-mannose used in this study showed no significant inhibition but rather supported the growth and proliferation of both cell lines, suggesting that compounds from saccharide family do not always inhibit the cancer cell viability or may involve in different inhibition pathways. Overall, selective cytotoxic effect of KGM on HepG2 cells viability, proliferation and dielectric properties suggested KGM as a potential anti-cancer entity to be further studied for its therapeutic uses.